2020
DOI: 10.1002/kin.21443
|View full text |Cite
|
Sign up to set email alerts
|

Updated thermochemistry for renewable transportation fuels: New groups and group values for acetals and ethers, their radicals, and peroxy species

Abstract: We present new groups and group values for the gas-phase thermochemistry of ethers, polyethers, and acetals suited for combustion modeling. Our investigation comprises fuel species, their primary radicals, peroxy radicals, and hydroperoxide species. In total, 45 species are used for the parameterization of 14 groups, six of which are newly introduced here. Presently, calculated thermochemistry at the DLPNO-CCSD(T)/CBS(cc-pVTZ, cc-PVQZ) // B3LYP-D3BJ/def2-TZVP level of theory is combined with thermochemistry fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…All calculated rate constants for the unimolecular decomposition and the β-scission reaction of Q ̇2OOHc are also visualized in the Supporting Information (section S5.1.1). 16 Furthermore, for the fuel fragments generated during the unimolecular decomposition and for the three fuel peroxyl radicals (RO ̇2) relevant to the low-temperature oxidation, the parameters were adopted from the theoretical work of Dontgen et al 52 The structure of DEM with the assignment of the corresponding radical positions and bond strength is shown in Figure 1. The naming convention in this work will follow the indicated numbering of the carbon atoms.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…All calculated rate constants for the unimolecular decomposition and the β-scission reaction of Q ̇2OOHc are also visualized in the Supporting Information (section S5.1.1). 16 Furthermore, for the fuel fragments generated during the unimolecular decomposition and for the three fuel peroxyl radicals (RO ̇2) relevant to the low-temperature oxidation, the parameters were adopted from the theoretical work of Dontgen et al 52 The structure of DEM with the assignment of the corresponding radical positions and bond strength is shown in Figure 1. The naming convention in this work will follow the indicated numbering of the carbon atoms.…”
Section: Methodsmentioning
confidence: 99%
“…Thermodynamic properties including enthalpies, entropies, and heat capacities are essential for the simulation of the oxidation and pyrolysis pathways of DEM. The thermochemical parameters for DEM (RH) and its three radicals (primary C–C site: Ṙ1 = C 2 H 5 OCH 2 OCH 2 ĊH 2 ; secondary C–C site: Ṙ2 = C 2 H 5 OCH 2 OĊHCH 3 ; and central O–C–O site: Ṙ4 = C 2 H 5 OĊHOC 2 H 5 ) are taken from the theoretical investigation of Kröger et al Furthermore, for the fuel fragments generated during the unimolecular decomposition and for the three fuel peroxyl radicals (RȮ 2 ) relevant to the low-temperature oxidation, the parameters were adopted from the theoretical work of Döntgen et al The structure of DEM with the assignment of the corresponding radical positions and bond strength is shown in Figure . The naming convention in this work will follow the indicated numbering of the carbon atoms.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For a direct comparison between the sensitivities on rate constants of reactions and enthalpies of formation of species, the optimization potentials of kinetic and thermochemical parameters were calculated following the work of vom Lehn et al, which are defined as products of parameter sensitivities and uncertainties. An uncertainty factor of 4 was assigned for the reaction rate constants, , as they were mostly specified by using rate rules. , A 2σ uncertainty of 8.18 kcal/mol was employed for the enthalpies of formation of species according to Döntgen et al, who reported a root-mean-square deviation with 1σ confidence interval of 4.09 kcal/mol between the enthalpies of formation calculated with the group additivity approach and the quantum mechanical method for ethers, polyethers, and acetals. The results are shown in Figures and .…”
Section: Future Research Perspectives and Challengesmentioning
confidence: 99%
“…A comprehensive assessment of the corresponding groups specific to alcohols and ethers is expected to be of highest priority. In particular, the thermochemical property values of hydroperoxy radicals of ethers can be significantly affected by hydrogen bond interactions between the hydroperoxy and the ether moieties, which deteriorates the prediction accuracy of conventional group values for those species and points to the need of further improvement, e.g., by consideration of additional non-nearest neighbor correction groups …”
Section: Future Research Perspectives and Challengesmentioning
confidence: 99%